The economic consequences of network neutrality regulation - Wagner, Andrew T. (Kansas State University, 2012)
The Internet is a network that consists of content providers and users connected to each other through the communication lines managed by network providers. Network neutrality rules are designed to protect independent content providers from unjust discrimination by network providers. This report explores the economic rationale for net neutrality rules, how the regulation should be enforced, and its potential effects on competition. The report finds that net neutrality encourages competition among content providers by subsidizing content provider access but concentrates the market for network providers by forcing network providers to compete primarily through price competition. It considers this to be a beneficial arrangement for economic growth, but observes that there is a potential for all sides of the market to be subsidized by advertiser fees. It also shows that despite the Federal Communications Commission's heavy involvement with network neutrality rules, these rules are actually based in a long history of antitrust regulation. It concludes, however, that the current regulatory environment is sufficient for enforcing net neutrality rules.
Keywords: Network neutrality; Regulation; Federal communications commission; Internet; Content providers; Business (0310); Economics (0501); Economics, Commerce-Business (0505)